Voices Unveiled: Law Students Speak Out on the Vital Significance of ESP Courses in Legal Education - Laksmita Rachmawati, Dwita; Budiarti, Dwi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study embarks on an exploration of the paramount significance of English for Specific Purposes (ESP) courses tailored for law students. A total of 40 second semester students taking ESP for law students at Universitas Merdeka Pasuruan participated in the survey after completing foundational legal English courses. Respondents were instructed to complete the questionnaires in 30 minutes to an hour to ensure a careful consideration of all survey issues before responding. The majority of respondents (33 students) expressed a high degree of agreement regarding the importance of ESP courses in enhancing their language proficiency. 55% or 22 students indicating highly content and 38% or 15 students expressing total satisfaction with the materials of the English for law class. 50% or 20 students stated that speaking is the most difficult skill among other 3 English skills. Essentially, it is advisable to mandate that students acquire a foundational understanding of legal knowledge before delving into the study of English for law. While law major needs to master the law paradigm, it is imperative when instructing an English for law class, instructors furnish information about their respective law concept.